Antimicrobial susceptibility testing of anaerobic bacteria: In routine and research. (June 2022) - Sood, Anshul; Ray, Pallab; Angrup, Archana
Abstract: To date, antimicrobial susceptibility testing (AST) in anaerobes is highly disarrayed. The testing is not routinely performed in many laboratories to direct appropriate antimicrobial therapy, and literature on AST remains scarce. This review aims to present the current methods employed for the AST of anaerobic bacteria both in routine and research. Anaerobes are potential human pathogens and predominate the human microbiota. Despite their significant role in human health and disease, they are not paid enough heed. The educated experience-based treatment has often been instituted with anaerobic infections due to the challenging AST and relatively predictable patterns of antimicrobial resistance (AMR). However, the AMR in anaerobes remains no more predictable, especially in Gram-negative anaerobes like Bacteroides spp., where multi-drug resistance is also emerging. The changing antibiograms and the emergence of resistance determinants in anaerobes necessitate routine AST, periodic monitoring, and literature review of these organisms. The present scenario dictates to limit the empirical management of anaerobic infections and encourage consistent AST practice in routine by employing economical, faster, and more pragmatic approaches, especially in tertiary care setups that cater to a vast patient population and are held accountable for producing accurate clinical and surveillance data. The article may provide a broad perspective on the topic and different AST solutions. Highlights: Anaerobic AST is undervalued and disorderly, mainly in the Indian subcontinent. Infrequent AST due to empirical management of anaerobes jeopardizes patient care. The emerging MDR in anaerobes calls for regular AST for guiding treatment. The article reviews the current methods of anaerobic AST in routine and research. The review also focuses on the specific clinical conditions that demand the AST.